Virtual donation management during the pandemic by Font Creator Berbagi - Habibi, Muhamad Lutfi (Manajemen Komunikasi, 2024)
This article explains the governance process of a virtual donation movement initiated by graphic designers in Indonesia during the COVID-19 pandemic called Font Creator Berbagi. This article aims to provide a deeper understanding of the management arrangements for the virtual donation movement, which is developing rapidly in the digital era. The novelty offered by this article is that it emphasizes studying the governance aspects of a social movement, which is more about material assistance, not skills training, which many graphic designers have previously done to channel their concerns during the pandemic. The qualitative method used in this research is a case study approach and data collection techniques through in-depth interviews whose questionnaires are based on the theory of POAC organizational management stages, according to George R. Terry. The research findings analyzed using the Miles and Huberman Model show that the Font Creator Berbagi movement has been successful in raising donations thanks to the stages that have been implemented, such as planning that is entirely aimed at charity, close organization by the community, implementation that prioritizes transparency, and supervision which focuses on digital infrastructure. Recommendations for similar social movements are to pay more attention to technical aspects, including choosing a more stable and reliable website hosting service to anticipate visits that exceed expectations. Apart from that, the potential for similar virtual donation movements will be increasingly being explored so further research opportunities can be opened.